SIFAT ORGANOLEPTIK MIE BERBAHAN DASAR TEPUNG JAGUNG (Zea mays L.) TERNIKSTAMALISASI - Nastri Dila Saniati; Siti Nurdjanah; Susilawati -; Nanti Musita (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2013)
This research was dedicated to study the organolepticproperties of nixtamalized corn starch noodles and to find thebest result from the duration needed in steeping process (0, 8,16, 24, and 32 hours). The research was a single factor,arranged in a Complete Randomized Design (RAKL) with fivereplications. The data were analyzed using ANOVA andfurther tested with LSD at 5% level of of significance. Theresult showed that duration of nixtamalization had significanteffects on color and overall acceptance of dry noodles as willas color of wet noodles. The best result was found on 8 hour ofthe steeping. This noodle had moisture content of 10.8% in theform of dry noodles and 62.1% in the form of wet noodles. Italso contained 1.7% ash, 1.1% fat, 3.7% protein, 82.8%carbohydrate, 8.7% non starch polysaccharide, and 3.5%cooking loss.Keywords: corn noodles, nixtamalized corn flour